2011
DOI: 10.1111/j.1365-2672.2011.05112.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Yersinia enterocolitica biotype 1A strain harbouring an ail gene

Abstract: Aims:  The chromosomal ail gene (attachment and invasion locus) is commonly used as target gene for the detection of pathogenic Y. enterocolitica strains in food testing. The ail PCR does not detect strains of biotype 1A (BT1A), which are regarded as non‐pathogenic because BT1A strains lack the virulence plasmid and chromosomally encoded virulence genes. In some recent reports, however, BT1A strains were discovered that harboured the ail gene. We isolated an ail‐positive strain and characterized this strain wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
(61 reference statements)
5
26
0
1
Order By: Relevance
“…One of these was validated in house and used during this monitoring programme (Mäde et al, 2008). The results of this study confirmed that the use of RT-PCR is a very useful tool for detecting only pathogenic bio(sero)types of Y. enterocolitica in food (Kraushaar et al, 2011;Miller et al, 1989).…”
Section: Discussionsupporting
confidence: 75%
“…One of these was validated in house and used during this monitoring programme (Mäde et al, 2008). The results of this study confirmed that the use of RT-PCR is a very useful tool for detecting only pathogenic bio(sero)types of Y. enterocolitica in food (Kraushaar et al, 2011;Miller et al, 1989).…”
Section: Discussionsupporting
confidence: 75%
“…However, the increasing isolation of this biotype from clinical cases draws more attention to BT1A [3;22]. Although rare, the presence of the ail- gene has previously been demonstrated in BT1A isolates [20;27]. The presence of the enterotoxin-gene ystB in combination with the ail- virulence gene could be an indication that these BT1A strains possess virulent characteristics [30].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the enterotoxin-gene ystB in combination with the ail- virulence gene could be an indication that these BT1A strains possess virulent characteristics [30]. However, potential loss of gene function, related to horizontal gene transfer cannot be ruled out [20]. The high genotypic diversity of BT1A makes the classification in clinical and non-clinical isolates more problematic since other, yet unknown, virulence factors could be contributing to the observed virulence in some strains [3;22;31].…”
Section: Resultsmentioning
confidence: 99%
“…2). The ail gene is often used to differentiate pathogenic from nonpathogenic Yersinia strains, even though ailpositive BT 1A isolates were recently reported, leading to the conclusion that methods which are exclusively based on the detection of ail genes are insufficient to distinguish between pathogenic and nonpathogenic strains (17,44,45). In contrast to our results, 14 out of 17 enteropathogenic Yersinia isolates recovered from wild boars shot between 2007 and 2008 in Switzerland were identified to be Y. enterocolitica and carriers of the chromosomal virulence gene marker ail (19).…”
Section: Resultsmentioning
confidence: 99%